Synthesis, Characteristics of CMK-3 Carbon Materials Derived on Various SBA-15 Templates and their Application in Electrochemical Supercapacitors - Bui, Thi Thanh Huyen; Le, Thi Thu Hang (Old Journal, 2020)
In this work, mesoporous silica SBA-15 has been synthesized from pure chemicals at different stirring regimes (2, 6, 10 minutes) and hydrothermal temperatures (80, 100, 120oC). Then, ordered mesoporous carbon materials (CMK-3) with very high surface area and pore volume has been succesfully prepared by incipient wetness impregnation technique using sucrose as carbon source and SBA-15 as hard templates. The obtained results of SEM, TEM, XRD and BET analyses showed that the synthesized CMK-3 samples possessed ordered mesoporous structure, and existed amorphous phase. The CMK-3 materials were composed of short nanorods with a size of 800 nm, which is analogous to the SBA-15 templates. The measured cyclic voltammetry results demonstrated that the CMK-3/100 electrode with the SBA-15 template synthesized at 100oC exhibited the excellent supercapacitive behavior in 6 M KOH electrolyte with a highest specific capacitance of 95.8 F/g.